2009
DOI: 10.1088/1741-2560/6/2/026005
|View full text |Cite
|
Sign up to set email alerts
|

In vivoevaluation of a neural stem cell-seeded prosthesis

Abstract: Neural prosthetics capable of recording or stimulating neuronal activity may restore function for patients with motor and sensory deficits resulting from injury or degenerative disease. However, overcoming inconsistent recording quality and stability in chronic applications remains a significant challenge. A likely reason for this is the reactive tissue response to the devices following implantation into the brain, which is characterized by neuronal loss and glial encapsulation. We have developed a neural stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 61 publications
(97 reference statements)
0
49
0
3
Order By: Relevance
“…3(c)). Alternatively, a completely open channel, i.e., no backside, can be used for stem-cell delivery with a dip coating technique (Purcell et al 2009). These cell-delivery structures now incorporate functional electrode sites.…”
Section: Resultsmentioning
confidence: 99%
“…3(c)). Alternatively, a completely open channel, i.e., no backside, can be used for stem-cell delivery with a dip coating technique (Purcell et al 2009). These cell-delivery structures now incorporate functional electrode sites.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work from Purcell et al (2009) confirmed that cell-seeded cortical probes have a beneficial effect on the early brain tissue response after implantation. They fabricated parylene devices, which were built-up by an open well seeded with mouse cortical neural stem cells encapsulated in an alginate hydrogel scaffold (Purcell et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
“…They fabricated parylene devices, which were built-up by an open well seeded with mouse cortical neural stem cells encapsulated in an alginate hydrogel scaffold (Purcell et al, 2009). The study, carried out in a rat model, described an improved healing process over a period of 3 month post-implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Parylene-C, PDMS and ITO are all transparent, biocompatible candidate materials for the fabrication of “next-generation” electrode arrays[9]–[12]. Each substrate offers unique advantages in addition to their superior optical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Each substrate offers unique advantages in addition to their superior optical properties. Parylene-C is commonly used as an encapsulation material as it is an electrical insulator which is also biologically and chemically inert [9], [10]. As such, it is a useful barrier to protect electrical components from biological environments while isolating tissue from the potentially toxic products of electrode degradation[10].…”
Section: Discussionmentioning
confidence: 99%